2009
DOI: 10.1002/jmv.21464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus and risk factors in Brazilian non‐injecting drug users

Abstract: Non-injecting drug users are at high-risk for acquiring hepatitis B virus (HBV), although the factors contributing to this increased risk are not known. In the present study, the overall and occult HBV infection prevalence rates were determined in a large population of non-injecting drug users in the Central-West region of Brazil. HBV genotypes and predictors of infection were also identified. A total of 852 individuals in 34 drug treatment centers were interviewed, and their serum samples were tested for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
24
2
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
9
24
2
11
Order By: Relevance
“…In our study, only 19.5% of participants presented a serological profile of prior immunization, confirming the low frequency of hepatitis B vaccination among vulnerable populations in our region and elsewhere 16,19,20,21 . However, it should be noted the wide variation observed in the distribution by age group, with prevalence of 53.6% in individuals aged 18 to 30 years dropping to 1.4% among those aged above 50 years.…”
Section: Variable Adjusted Pr (95%ci) P-valuesupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, only 19.5% of participants presented a serological profile of prior immunization, confirming the low frequency of hepatitis B vaccination among vulnerable populations in our region and elsewhere 16,19,20,21 . However, it should be noted the wide variation observed in the distribution by age group, with prevalence of 53.6% in individuals aged 18 to 30 years dropping to 1.4% among those aged above 50 years.…”
Section: Variable Adjusted Pr (95%ci) P-valuesupporting
confidence: 79%
“…Age (years) 15 and users of illicit drugs (n = 852; 14%; 95%CI: 11.7-16.5) 16 . However, the prevalence found among homeless people in Goiânia was lower than that found ten years before by Brito et al 7 (30.6%; 95%CI: 25.9-35.8) in São Paulo.…”
Section: Variable Adjusted Pr (95%ci) P-valuementioning
confidence: 99%
“…Compared with the prevalence in other Brazilian populations, the prevalence determined in this study was within the confi dence interval range recorded for patients attending an STD clinic (13%; 95% CI: 10.0-16.5) 20 , non-injection drug users (14%; 95% CI: 11.7-16.5) 21 and individuals reporting to an HIV testing and counseling center (14.6%; 95% CI: 11.2-18.0) 22 . Nevertheless, relative to other reported data on recyclable waste collectors, the prevalence found in the present study was lower than that observed in Santos, Brazil (34.4%; 95% CI: 28.5-40.2) 14,15 .…”
Section: Discussionsupporting
confidence: 62%
“…Among the 71 recyclable waste collectors who reported illicit drug use, the majority had used non-injection drugs only (88.7%; 63/71) (data not shown). Although the factors leading to an increased risk of hepatitis B in non-injection drug users are not well established, HBV infection is associated with unsafe sexual behavior and blood-borne transmission 21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…No similar reports from Brazil were available for comparative purposes, but the prevalence of occult HBV infection measured in this study was higher than that observed in a population of non-IDUs in the Central-West Region of Brazil (2.7%, CI 95%: 0.7-8.3) (Ferreira et al 2009). Nevertheless, the prevalence observed in this study is comparable to those observed in IDU populations Italy (3.2%, CI 95%: 0.5-12.1) (Vitale et al 2008) and Argentina (7.7%, CI 95%: 3.9-14.0) (Trinks et al 2008).…”
contrasting
confidence: 74%